2005
DOI: 10.1161/01.atv.0000153106.03644.a0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Phospholipids Trigger Atherogenic Inflammation in Murine Arteries

Abstract: Objective-Lipoprotein-derived phospholipid oxidation products have been implicated as candidate triggers of the inflammatory process in atherosclerosis. However, in vivo evidence regarding the impact of oxidized phospholipids on the artery wall thus far has been elusive. Therefore, the aim of this study was to investigate if structurally defined oxidized phospholipids induce expression of atherogenic chemokines and monocyte adhesion in intact murine arteries. Methods and Results-To model the accumulation of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 53 publications
3
101
0
Order By: Relevance
“…It is well known in cardiovascular biology that a diet high in fat promotes atherogenesis (32) by increasing levels of lipid oxidation products, (4,5) especially in genetically hyperlipidemic subjects. It is now recognized that such a diet also reduces bone density, (9,18,19) promotes bone resorptive activity, (2,9,33,34) and importantly, interferes with parenteral PTH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known in cardiovascular biology that a diet high in fat promotes atherogenesis (32) by increasing levels of lipid oxidation products, (4,5) especially in genetically hyperlipidemic subjects. It is now recognized that such a diet also reduces bone density, (9,18,19) promotes bone resorptive activity, (2,9,33,34) and importantly, interferes with parenteral PTH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To delineate whether TNF-a also suppressed expression of SMC marker genes and activated expression of pro-inflammatory/ matrix-remodeling genes in vivo, the F-127 pluronic gel system 20,21 was used to apply TNF-a or vehicle to the adventitial surface of rat carotid arteries in vivo ( Figure 1). Quantitative realtime RT-PCR analysis demonstrated that TNF-a induced significant suppression of SM-a-actin, SM-MHC, and SM-22-a after 24 hours as well as a significant increase in KLF4 mRNA levels after 6 hours of treatment, vs vehicle-treated vessels (Supplementary Figure 4A).…”
Section: Tumor Necrosis Factor-alpha Decreased Expression Of Smooth Mmentioning
confidence: 99%
“…PAPC also induces monocyte adhesion and inflammation in atherosclerotic mice in vivo [26]. Several studies, including some conducted in vivo, have demonstrated that oxidized phospholipids can influence many of the processes involved in vascular remodelling such as VSMC proliferation, migration and ECM production [27][28][29][30].…”
Section: Apoementioning
confidence: 99%